2004
DOI: 10.1590/s0034-70942004000500012
|View full text |Cite
|
Sign up to set email alerts
|

O plantão noturno em anestesia reduz a latência ao sono

Abstract: RESUMO dias anteriores ( M 3 ) . E m t o d a s e s s a s s i t u a ç õ e s f o i r e a l i za d o eletroencefalograma (EEG) contínuo, em sala apropriada para registro dos sinais de sono, avaliando a latência ao sono (LS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
0
5
0
5
Order By: Relevance
“…In Brazil, though the law (Decreto 80.281/1977) already restricts the work week to 60 hours, with 80 to percent assigned to service and the rest to classroom and complementary work, several studies find major health issues secondary to prolonged duty hours, including burnout syndrome, depression, fatigue, stress, and anxiety 8,15,[33][34][35][36][37] . The results tell us the service and resident training should be reformed to improve the quality of life of residents, thus improving the quality of patient care in Brazilian health care facilities.…”
Section: Stress Among Residentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, though the law (Decreto 80.281/1977) already restricts the work week to 60 hours, with 80 to percent assigned to service and the rest to classroom and complementary work, several studies find major health issues secondary to prolonged duty hours, including burnout syndrome, depression, fatigue, stress, and anxiety 8,15,[33][34][35][36][37] . The results tell us the service and resident training should be reformed to improve the quality of life of residents, thus improving the quality of patient care in Brazilian health care facilities.…”
Section: Stress Among Residentsmentioning
confidence: 99%
“…Studies about coping strategies have shown that almost half of all residents have problems coping with emotional stress, which has a negative impact on the doctorpatient relationship and on performance, thus proving the need for strategies to help residents cope with stress. 33,34 Blandin et al 33 stress that medical residents with dysfunctional coping strategies are more susceptible to burnout syndrome.…”
Section: Stress Among Residentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neste sentido, estudos têm demonstrado que a implementação de programas de assistência aos residentes produz uma melhoria tanto na qualidade da capacitação profissional, em termos de lidar com o estresse do treinamento, como também na qualidade de vida pessoal, com um melhor relacionamento com os pacientes. 30,31 Ainda, o fato da Residência Multiprofissional em Saúde ser um período marcado por longas jornadas de trabalho e estudo e pouco tempo para descanso, uma vez que o programa é desenvolvido em regime de dedicação exclusiva com carga horária de 60 horas semanais, pode interferir de forma negativa na qualidade do sono. Isto foi confirmado no presente estudo, já que o grupo de R2 em sua maioria (72,22%) apresentou uma qualidade ruim do sono em contraponto ao grupo RIn, que em sua maioria (83,33%) não apresentou alteração no sono.…”
Section: Tabela 3: Valores Médios Das Dimensões Do Mbi E Análise Entrunclassified
“…Anesthesiology is among the specialties affected by this problem 31 . The responsibility imposed on it can be considered a stress factor for the professional on duty, generating malaise, sleep disturbances, excessive tiredness, irritability, restlessness, low tolerance to frustration, impatience, feelings of depression, and depersonalization, leading to affective detachment and apathy 32,33 . In the fi eld of anesthesiology, there are other factors that also cause high stress, such as time constraints, interference in personal and family life, medical legal aspects, miscommunication with colleagues, possibility of clinical complications in the perioperative period, little professional recognition, prolonged work shifts, responsibility for any complications, and unrealistic professional expectations 34 .…”
Section: Occupational Diseasesmentioning
confidence: 99%